2012
DOI: 10.1002/per.855
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Bias Modification Using Mental Imagery for Depression: Developing A Novel Computerized Intervention to Change Negative Thinking Styles

Abstract: Why do some people see their glass as half-empty rather than half-full or even imagine that the glass will be filled in the future? Experimental methods can illuminate how individual differences in information processing style can profoundly impact mood or even result in disorders such as depression. A computerized cognitive bias modification intervention targeting interpretation bias in depression via positive mental imagery (CBM-I) was evaluated by investigating its impact on mental health and cognitive bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
161
4
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(191 citation statements)
references
References 90 publications
(152 reference statements)
11
161
4
1
Order By: Relevance
“…Given the maintaining role of information processing biases, it is important to consider the potential value of targeted cognitive training that can either train neural structures known to be impaired in depression (Siegle et al, 2007) or modify emotion specific biases in attention (Baert, De Raedt, Schacht, & Koster, 2010;, interpretation (Blackwell & Holmes, 2010;Holmes, Lang, & Shah, 2009;Lang, Blackwell, Harmer, Davison, & Holmes, 2011) or memory (Joormann, Hertel, LeMoult, & Gotlib, 2009;Raes et al, 2009). In general, cognitive bias modification (CBM) methodologies target specific cognitive processes by exposing participants to experimentally established contingencies during a task designed to encourage the acquisition or attenuation of an information processing bias ).…”
Section: Modification Of Cognitive Biasesmentioning
confidence: 99%
“…Given the maintaining role of information processing biases, it is important to consider the potential value of targeted cognitive training that can either train neural structures known to be impaired in depression (Siegle et al, 2007) or modify emotion specific biases in attention (Baert, De Raedt, Schacht, & Koster, 2010;, interpretation (Blackwell & Holmes, 2010;Holmes, Lang, & Shah, 2009;Lang, Blackwell, Harmer, Davison, & Holmes, 2011) or memory (Joormann, Hertel, LeMoult, & Gotlib, 2009;Raes et al, 2009). In general, cognitive bias modification (CBM) methodologies target specific cognitive processes by exposing participants to experimentally established contingencies during a task designed to encourage the acquisition or attenuation of an information processing bias ).…”
Section: Modification Of Cognitive Biasesmentioning
confidence: 99%
“…Previous studies (Nordin and Cumming, 2005;Lang et al, 2011) show large average effects (Cohen, 1992) for pre-post change (f=0.34) and group x time interactions (f=0.45), suggesting a total sample size in excess of n=36 to achieve 90% power, with alpha adjusted to 0.01 to take account of multiple testing (Faul et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Taking into account the methodological limitations of previous studies, researchers have confirmed the value of repeated CBM-I in reducing depressive symptomatology in MDD populations [36,37]. Interestingly, Williams, Blackwell, Mackenzie, Holmes, and Andrews [38] have demonstrated the (partially) mediating effect of change in interpretation bias on the reduction of depressive symptomatology following CBM-I.…”
Section: Interpretation Bias Modificationmentioning
confidence: 98%